Tremorography in the clinical practice - T. G. Govorova; T. E. Popova; A. A. Tappakhov (Нервно-мышечные болезни, 2020)
Tremor is the most common type of movement disorders. In practice this differential diagnosis of hyperkinesis is diagnosed clinically and the use of additional methods of objective assessment of tremor increases the accuracy of diagnosis. The use of paraclinical methods of objective assessment of tremor improves the accuracy of diagnosis. Comparison of the neurophysiological parameters of tremor with clinical characteristics has a high diagnostic value, which justifies its use in the routine practice of neurologists. The purpose of the review is to analysis basic electrophysiological characteristics of pathological tremor, as well as the presentation of the material of its own observation.